2021
DOI: 10.3847/1538-4357/ac1419
|View full text |Cite
|
Sign up to set email alerts
|

Breaching the Limit: Formation of GW190521-like and IMBH Mergers in Young Massive Clusters

Abstract: The LIGO-Virgo-Kagra collaboration (LVC) discovered recently GW190521, a gravitational wave (GW) source associated with the merger between two black holes (BHs) with mass 66 M and > 85 M . GW190521 represents the first BH binary (BBH) merger with a primary mass falling in the "upper mass-gap" and the first leaving behind a ∼ 150 M remnant. So far, the LVC reported the discovery of four further mergers having a total mass > 100 M , i.e. in the intermediate-mass black holes (IMBH) mass range. Here, we discuss re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…First, they can accelerate the merging of compact object binaries, allowing them to merge within the age of the Universe. Secondly, they excite very high eccentricity in the inner compact binary, which can affect the GW emission waveform, and therefore can be potentially inferred by GW observations at different frequencies [446][447][448]. The evolution in triple systems can also be affected by all the processes that occur in binary stars, and more.…”
Section: Small-n Systemsmentioning
confidence: 99%
“…First, they can accelerate the merging of compact object binaries, allowing them to merge within the age of the Universe. Secondly, they excite very high eccentricity in the inner compact binary, which can affect the GW emission waveform, and therefore can be potentially inferred by GW observations at different frequencies [446][447][448]. The evolution in triple systems can also be affected by all the processes that occur in binary stars, and more.…”
Section: Small-n Systemsmentioning
confidence: 99%
“…A further possibility is that the IMBH growth is regulated by both processes above: first an IMBH seed with a mass > 100 M forms via stellar collisions or accretion onto stellar BHs and later the IMBH grows further via repeated BH mergers (e.g., Arca-Sedda et al 2021;Rizzuto et al 2021b). Assuming that a population of IMBH seeds with masses in the range 100 − 500 M formed in globular clusters at redshift z = 2 − 6 (Katz & Ricotti 2013), recently Arca have shown that the overall population of IMBHs at redshift z < 1 would be characterized by a mass distribution that extends between 250 − 1500 M , with a clear peak at around M IMBH ∼ 750 M .…”
Section: Implications Of Spectral Analysismentioning
confidence: 99%
“…Furthermore, a number of recent observations have linked TDEs of white dwarfs by massive black holes with massive star clusters (e.g., Krolik & Piran 2011;Jonker et al 2013;Lin et al 2018) Aside from their intrinsic interest as electromagnetic transient sources, close encounters between black holes and stars may have an important effect on the overall demographics of black holes in clusters. If a significant fraction of the disrupted stellar material is accreted by the black hole, these TDEs may lead to significant black hole mass growth, potentially enabling formation of black holes within or above the pair-instability mass gap (e.g., Giersz et al 2015;Rizzuto et al 2021;Arca-Sedda et al 2021;Rose et al 2021). Furthermore, if a star is disrupted by a binary black hole, the disrupted material may alter the spin magnitude and orientation of the binary black hole components (e.g., Lopez et al 2019).…”
Section: Introductionmentioning
confidence: 99%